АНАЛІЗ ВПЛИВУ ПЛАНУ ТА ПОЗДОВЖНЬОГО ПРОФІЛЮ КОЛІЇ НА УМОВИ ЕКСПЛУАТАЦІЇ КОНТРЕЙЛЕРНИХ ПОЇЗДІВ - Kuzmenko, Albina I.; Muzykin, Mykhailo I.; Nesterenko, Halyna I.; Strelko, Oleg G. (Systems and Technologies, 2022)
Summary. In this paper, the influence of the plan and longitudinal profile of the track on the operating conditions of piggyback trains is analyzed. The economic indicators of the organization of piggyback trains in the direction Lviv – Mukachevo are determined and compared with the indicators of road transport on the route between the same cities. An analysis of recent research and publications on the development of piggyback transport shows that further research in this area is necessary and relevant. The experience and practice of piggyback transportation has shown their feasibility and advantages. As you know, container transportation is the transportation of loaded trucks or semi-trailers on special railway platforms. That is, this part of the road meets the basic rules for determining the technical, operational and economic performance of railway transport. It should be noted that on the railways, the indication of the group of indicators, including the cost of transportation, among other factors, is significantly influenced by the plan and profile of the track. Therefore, in this paper, the plan and longitudinal profile of the railway line is presented as a combination of individual real reference sections of the specified direction, within which the piggyback transport is carried out. According to the results of calculations of the volumes of possible cargoes, directions of transportations and terminals where it will be possible to carry out loading and unloading of pigtails, perspective directions of piggyback trains have been established. Histograms of the distribution of slopes and curves in the sections Lviv – Stryi, Stryi – Lavochne, Lavochne – Mukachevo were constructed. The results of traction and operational calculations are given. The train of the established lengths with evenly distributed weight is accepted as calculation model. The settlement train consists of a locomotive, two passenger cars for drivers and forty or twenty long-base platforms loaded with road trains. A system of criteria for the evaluation of direct road and combined (piggyback) transportation is proposed. Two variants of cargo delivery organization between Lviv and Mukachevo are compared: automobile and piggyback. The dependence of the cost of transportation and reduced costs on their range for road and piggyback transportation at a technical speed of 50 km/h. Further scientific research may be aimed at improving the technical component that affects the economic attractiveness of piggyback transport for domestic and foreign indicators. After all, the development of this type of transportation will help strengthen Ukraine’s competitive position in the European logistics market.